Use of Some Asteraceae Plants for the Treatment of Wounds: From Ethnopharmacological Studies to Scientific Evidences - Carvalho, Alexsander R.; Diniz, Roseana M.; Suarez, Mariela A. M.; Figueiredo, Cristiane S. S. e S.; Zagmignan, Adrielle; Grisotto, Marcos A. G.; Fernandes, Elizabeth S.; da Silva, Luís C. N. (Frontiers in Pharmacology, 2018)
Severe wounds are responsible for larger lesions and/or loss of function of the affected region. The treatment of wounds have been challenging health professionals due its complexity, especially in patients with chronic diseases (such as diabetes) and the presence of pathogens such as Staphylococcus aureus and Pseudomonas aeruginosa. In this context, the development of new therapies for wound healing is an urgent need. Ethnopharmacological studies performed in different countries have shown the use of several plants from Asteraceae family as healing agents for treatment of different types of wound. The traditional knowledge has been exploited for the development of new efficient therapies based on these plants. This manuscript highlights the scientific evidences for use of agents derived from Asteraceae plants for healing treatment. Especial focus is given for those papers that revealed the action mechanisms of isolated compounds and for clinical trials. Several in vitro and in vivo models have demonstrated the healing activities of several compounds. Ageratina pichinchensis and Calendula officinalis have shown good results in clinical trials for treatment of complicated wounds as for healing of venous leg ulcers and ulcers at foot of diabetic patients. Further, the compounds Silibinin (from Silybum marianum) and Jaceosidin (from Artemisia princeps) are pointed as promise compounds for the development of healing agents. In summary, Asteraceae plants are promising targets for the development of new efficient drugs for healing. Furthermore, these studies may help the improvement of our knowledge about the healing process.